Prevalence of CYP2C19 variant alleles and pharmacodynamic variability of aspirin and clopidogrel in Native Americans - Oestreich, Julie H.; Best, Lyle G.; Dobesh, Paul P. (The American heart journal, 2014)
The prevalence of variant alleles of the CYP2C19 gene has been determined for most population groups, but not Native Americans. Furthermore, the overall effectiveness of clopidogrel and aspirin has not been well studied in Native Americans, although this group has high mortality rates for cardiovascular disease and diabetes. We recruited 50 volunteers from the Oglala Sioux Tribe with coronary artery disease taking aspirin and clopidogrel. Whole blood was collected for analysis using the VerifyNow P2Y12 and aspirin tests. Samples from the coronary artery disease patients and 50 additional tribal volunteers (n = 100 total) were genotyped for CYP2C19 variants *2, *3, and *17. The allele frequencies for CYP2C19*2 and CYP2C19*17 in the population group were 11% (95% CI 7%-16%) and 9% (95% CI 5%-13%), respectively. No subjects carried the CYP2C19*3 allele. The median PRU (P2Y12 reaction units) in the population group was 194 with wide variability (range 29-400). There was no significant effect of genotype on platelet aggregation as measured by the VerifyNow P2Y12 test (P = .77). The median ARU (aspirin reaction units) for the group was 437 (range 350-659), and 73% had aspirin reaction unit values <550. The prevalence of variant CYP2C19 alleles is low in Native Americans of the Oglala Sioux Tribe compared with certain HapMap populations. The variable response to aspirin and clopidogrel in the Oglala Sioux Tribe is consistent with reported values for other groups as measured by the VerifyNow assay (Accumetrics, San Diego, CA).